Evaluation of Susceptibility of the Human Pathogen Helicobacter pylori to the Antibiotic Capreomycin. (31st July 2022) - Sukati, Suriyan; Sama-ae, Imran; Katzenmeier, Gerd; Wisessombat, Sueptrakool
Abstract : Helicobacter pylori infection causes gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue lymphoma, and gastric cancer and can also promote thrombosis. It is estimated that approximately 4.5 billion individuals are infected, thus rendering H. pylori the most prevalent microbial pathogen. Currently established regimes for antibiotic treatment are massively challenged by increasing drug resistance and the development of novel antimicrobial therapies is urgently required. The antibiotic capreomycin is clinically used against multiple drug-resistant strains of Mycobacterium tuberculosis . It targets the complex between TlyA, a hemolysin- and RNA-binding protein, and the bacterial rRNA. In this study we have explored the possible antibacterial effects of capreomycin against several strains of H. pylori and found only moderate activity which was comparable to metronidazole-resistant strains. Molecular docking of capreomycin to TlyA proteins from H. pylori and M. tuberculosis identified several residues within TlyA which interact with the drug; however, binding affinities of H. pylori – TlyA for capreomycin appear to be higher than those of Mycobacterium – TlyA. The data suggest that capreomycin may warrant further investigations into its potential use as antibiotic against H. pylori.